Fish ring microhabitats: Resilience in rice field fisheries - WorldFish (2014)
A habitat is the environment where species such as fish live, feed and breed. A small, specialized area of a habitat—a microhabitat—can be created and managed as a way to attract and encourage a species to use the environment. These microhabitats help maintain the biodiversity of ecosystems, which in turn support livelihood activities and the production of food.